Neural BC1 RNA as an evolutionary marker: guinea pig remains a rodent. - Martignetti, J A (1993)
The traditional morphologically grounded placement of South American guinea pig-like rodents (Caviomorpha) within one of the two rodent suborders, Hystricognathi, has been disputed by recent analysis of protein and nucleic acid sequence data. The Caviomorpha and possibly all Hystricognathi would be considered a separate order, distinct from the other rodent suborder, Sciurognathi, and thus of the order Rodentia, and would be placed closer phylogenetically to other mammals [Graur, D., Hide, W. A. & Li, W.-H. (1991) Nature (London) 351, 649-652]. To address the discrepancy between morphological comparisons and sequence analyses, we have applied an alternative form of molecular analysis. We demonstrate that BC1 RNA, a neural-specific small cytoplasmic RNA that is the product of a retropositionally generated gene (a gene derived by reverse transcription of RNA followed by insertion of the DNA copy into the genome), is present in Sciurognathi and guinea pig but not in other mammalian orders including Lagomorpha, Artiodactyla, and Primates. The species-confined, tissue-specific expression of a retroposed sequence therefore supports the morphological evidence for monophyly of Rodentia inclusive of guinea pig and demonstrates the usefulness of such molecular genetic markers. Furthermore, the conservation and tissue-specific expression of the BC1 RNA gene in the two divergent rodent suborders suggests that this macromolecule has been exapted into a functional role (i.e., coopted into a variant or novel function) in the rodent nervous system.